2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Poor performance of the modified early warning score for predicting mortality in critically ill patients presenting to an emergency department

Abstract: BACKGROUND: This study was undertaken to validate the use of the modified early warning score (MEWS) as a predictor of patient mortality and intensive care unit (ICU)/ high dependency (HD) admission in an Asian population. METHODS:The MEWS was applied to a retrospective cohort of 1 024 critically ill patients presenting to a large Asian tertiary emergency department (ED) between November 2006 and December 2007. Individual MEWS was calculated based on vital signs parameters on arrival at ED. Outcomes of mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 7 publications
0
35
1
Order By: Relevance
“…We investigated the reliability of NEWS cut‐offs for specific patient groups, as some concerns on its validity were raised in the literature . Debate raised about the accuracy of EWS performance in different races and patient subpopulations . For this reason, modifications of NEWS have been suggested by some authors to improve specificity whilst identifying the sickest patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the reliability of NEWS cut‐offs for specific patient groups, as some concerns on its validity were raised in the literature . Debate raised about the accuracy of EWS performance in different races and patient subpopulations . For this reason, modifications of NEWS have been suggested by some authors to improve specificity whilst identifying the sickest patients …”
Section: Discussionmentioning
confidence: 99%
“…16 Debate raised about the accuracy of EWS performance in different races and patient subpopulations. 27 For this reason, modifications of NEWS have been suggested by some authors to improve specificity whilst identifying the sickest patients. 18,28 Our analysis evidenced that a number of cardiac conditions might cause acute worsening without generating higher NEWS scores on admission, as unplanned transfers owing to sudden cardiac events occurred mainly for low and medium category of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Different risk scoring systems for the triage of emergency patients have been described [1319], but their performances outside the contexts and settings used in their validations cannot be warranted [20]. Furthermore, several of these models were designed to be used in a non-surgical ED and cannot be used in our surgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Region-specific equations or adaptations for resource-limited settings can improve performance and facilitate implementation [55][56][57][58][59]. Risk assessment tools, such as the Modified Early Warning Score, which might help triage critically patients and allocate resources [54] have shown conflicting results when applied in resource-limited settings and need additional modifications and validation [60,61].…”
Section: Gaps In Evidence For Best Practicesmentioning
confidence: 99%
“…In one ICU in Tanzania, an observational study showed that detection of vital sign derangements infrequently led to treatment modifications [80] and led the authors to conclude that nursing-based vital signs-directed clinical response protocols may not improve outcomes in resource-limited setting. Early warning systems have been shown to be predictive in some [54] but not all settings [60,61], underscoring the need for further development and validation in resource-limited settings.…”
Section: Early Recognition and Treatment Of Critical Illnessesmentioning
confidence: 99%